The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1002/cncr.28309
|View full text |Cite
|
Sign up to set email alerts
|

Clinical significance of circulating tumor cells in peripheral blood from patients with gastric cancer

Abstract: BACKGROUND The authors hypothesized that circulating tumor cells (CTCs) in patients with gastric cancer are associated with prognosis and disease recurrence. In this study, they evaluated CTCs in gastric cancer and clarified the clinical impact of CTCs. METHODS In total, 265 consecutive patients with gastric cancer were enrolled. Fourteen patients were excluded from the analysis, including 12 patients who another cancer and 2 patients who refused the treatment. The remaining 251 patients were divided into 2 gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
81
4

Year Published

2014
2014
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 82 publications
(91 citation statements)
references
References 20 publications
6
81
4
Order By: Relevance
“…reported that progression‐free survival was significantly shorter in patients with than in those without CTC ( P  = 0.016). All other studies based on the CellSearch system demonstrated that CTC had an influence on prognosis 48, 49, 51. These findings suggest that the presence or absence of CTC has an effect on the prognosis of patients with gastric cancer, even in cytometric‐based methods.…”
Section: Prognostic Impact Of Ctcmentioning
confidence: 80%
See 3 more Smart Citations
“…reported that progression‐free survival was significantly shorter in patients with than in those without CTC ( P  = 0.016). All other studies based on the CellSearch system demonstrated that CTC had an influence on prognosis 48, 49, 51. These findings suggest that the presence or absence of CTC has an effect on the prognosis of patients with gastric cancer, even in cytometric‐based methods.…”
Section: Prognostic Impact Of Ctcmentioning
confidence: 80%
“…47–55 The CellSearch system was previously used to detect CTC in four (44.4%) out of nine studies using cytometric‐based assays. The findings of these CellSearch studies demonstrated that the incidence of CTC ranged between 10.8% and 18.4% and between 32.7% and 60.2% in patients with stages I–IV and stage IV, respectively 48, 49, 51, 53. These findings indicate that incidence of CTC is higher in patients with than in those without distant metastasis.…”
Section: Incidence Of Ctcmentioning
confidence: 91%
See 2 more Smart Citations
“…[65] 2013 93 RT-PCR STC2 The 5-year OS rate was significantly lower in patients with STC2 expressioncompared to patients without STC2 expression Uenosono et al . [66] 2013 148 CellSearch EpCAM, CK8, 18, 19…”
Section: Heterogeneity Of Ctcsmentioning
confidence: 99%